Homologous and Heterologous Chiral Supramolecular Polymerization from Exclusively Achiral Building Blocks. (8th August 2022) - Li, Chengxi; Sang, Yutao; Jin, Xue; Duan, Pengfei; Liu, Minghua
Abstract: Among the enticing issues of chiral origins are: how chirality is born from the initial achiral units and the mechanisms for the transfer of chiral information. In this work, by combining a physical vortex and chiral seeds, a general process is revealed to generate chiral supramolecular polymers from achiral C 3 ‐symmetric molecules. The symmetry‐broken assemblies from the achiral molecules could work as chiral seeds to initiate the polymerization of either homologous or heterologous achiral monomers. Concomitantly, the fragmentation of the polymer caused by the vortex during the nucleation‐elongation stages is shown to enlarge the domains of the chiral nuclei and then guide the polymer to grow into the predominant helicity with a high reactivity ratio. Moreover, the chiral structural information can be stored in different forms of assemblies. These new polymerization modes will provide guidance for the preparation of chiral materials. Abstract : Achiral C 3 ‐symmetric monomers have been used to build chiral supramolecular polymer architectures by a symmetry‐breaking process in a vortex. Subsequently, the polymers can take the role of chiral seeds to control the ensuing homologous or heterologous chiral supramolecular polymerization.